2010
DOI: 10.1029/2008jg000913
|View full text |Cite
|
Sign up to set email alerts
|

Annual cycle of methane emission from a subarctic peatland

Abstract: [1] Although much attention in recent years has been devoted to methane (CH 4 ) emissions from northern wetlands, measurement based data sets providing full annual budgets are still limited in number. This study was designed to help fill the gap of year-round measurements of CH 4 emissions from subarctic mires. We report continuous eddy correlation CH 4 flux measurements made during 2006 and 2007 over the Stordalen mire in subarctic Sweden (68°20′N, 19°03′E, altitude 351 m) using a cryocooled tunable diode las… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

20
136
3

Year Published

2012
2012
2015
2015

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 144 publications
(159 citation statements)
references
References 32 publications
(48 reference statements)
20
136
3
Order By: Relevance
“…5d). This conclusion is consistent with the field results (e.g., Bäckstrand et al, 2008;Jackowicz-Korczyński et al, 2010). As illustrated by Fig.…”
Section: Water Table and Ch 4 Fluxessupporting
confidence: 82%
See 1 more Smart Citation
“…5d). This conclusion is consistent with the field results (e.g., Bäckstrand et al, 2008;Jackowicz-Korczyński et al, 2010). As illustrated by Fig.…”
Section: Water Table and Ch 4 Fluxessupporting
confidence: 82%
“…The simulations of average accumulated CH 4 fluxes over non-growing seasons were 9.8 and 13.8 kg CH 4 -C ha −1 at the sphagnum and eriophorum sites, representing 30 and 13 % of mean annual emissions. In the wet area dominated by tall graminoid vegetation, field measurements demonstrated that CH 4 emissions over winter accounted for approximately 19 % of the annually emitted CH 4 (Jackowicz- Korczyński et al, 2010). These results indicate that further tests are necessary to verify the model's predictions of C fluxes during winter periods.…”
Section: Validation Of Dndcmentioning
confidence: 94%
“…On the other hand, Baldocchi et al (2012) reported higher CH 4 emissions at night in a peatland pasture, owing to collapse of the nocturnal boundary layer and elongation of flux footprint to elevated CH 4 source areas in calm conditions. In a subarctic peatland dominated by tall graminoids, no diel cycle in CH 4 flux was seen throughout the year (Jackowicz-Korczyski et al, 2010). Some studies that used autochambers on wetlands have reported CH 4 or total hydrocarbon fluxes for time periods of a day or more Bäckstrand et al, 2010), making it hard to deduce the variability over shorter time periods from their results.…”
Section: Y F Lai Et Al: Atmospheric Turbulence and Chamber Deplmentioning
confidence: 87%
“…Finally, in analysing fluxes the quality flag classification system proposed by Foken et al (2004) was applied. The CH 4 fluxes were gap filled based on the exponential soil temperature relationship presented by Jackowicz-Korczyński et al (2010) while with the CO 2 flux signal two different approaches were applied. The daytime CO 2 fluxes recorded during the growing season were gap filled by applying the light response equation (1) while the rest of the fluxes were parameterized with the night respiration equation (2) (Falge et al 2001).…”
Section: Gap Fillingmentioning
confidence: 99%